2012
DOI: 10.4103/0970-9290.102220
|View full text |Cite
|
Sign up to set email alerts
|

The effect of remelting various combinations of new and used cobalt-chromium alloy on the mechanical properties and microstructure of the alloy

Abstract: Repeated remelting of base metal alloy for dental casting without addition of new alloy can affect the mechanical properties of the alloy. Microstructure analysis shows deterioration upon remelting. However, the addition of 25% and 50% (by weight) of new alloy to the remelted alloy can bring about improvement both in mechanical properties and in microstructure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…(2007) noticed a significant increase in Vickers hardness appearing in the fifth recast. Gupta and Mehta (2012) reported that repeated remelting of base metal alloy for dental casting without adding new alloy will affect the alloy properties. The increase in hardness reported in the work maybe due to intermetallic and carbide formation.…”
Section: Hardnessmentioning
confidence: 99%
See 1 more Smart Citation
“…(2007) noticed a significant increase in Vickers hardness appearing in the fifth recast. Gupta and Mehta (2012) reported that repeated remelting of base metal alloy for dental casting without adding new alloy will affect the alloy properties. The increase in hardness reported in the work maybe due to intermetallic and carbide formation.…”
Section: Hardnessmentioning
confidence: 99%
“…Reisbick and Brantley (1995) reported no significant diminishment in the tensile properties after recasting type III Gold (46%) alloy up to three times. However, Gupta and Mehta (2012) noticed compositional and physical changes along with decreased fluidity after remelting of base alloys. Harcourt and Cotterill (1965) suggested that the elements such as Co, Ni, Cu, Cr, Sn, Fe, and Zn could alter during recasting due to evaporation and oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…9 Alloy recasting in dentistry, without the addition of new alloys, can affect the mechanical properties and affect the microstructure of the alloy. 11 Fracture toughness is important in frame denture and recasting is also needed to obtain frame denture that can be applied in dentistry. Based on the abovementioned description, this study examined whether there is an effect of Co-Cr alloy recasting on fracture toughness.…”
Section: Introductionmentioning
confidence: 99%
“…Recasting with at least 50% of new alloy also does not affect the physico-chemical and mechanical properties of the alloys [15]. Some reports show that even 25% of new alloy could be used, when remelting only up to one or two times [16], while others state that using the contributions of scrap in castings deteriorates the strength properties substantially [17].…”
Section: Introductionmentioning
confidence: 99%